2019
DOI: 10.1002/aic.16604
|View full text |Cite
|
Sign up to set email alerts
|

Curvature dependence of Henry's law constant and nonideality of gas equilibrium for curved vapor–liquid interfaces

Abstract: Curved interfaces between coexisting vapor and liquid phases are ubiquitous in nature, and the question of whether the Henry's law is applicable for highly curved vapor/liquid interfaces remains unsolved. Using stable surface nanobubbles that have highly curved interfaces as examples, we investigate the viability of Henry's law with molecular simulations and thermodynamic analysis. We show that the prediction of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…14 where f 1 is the fugacity of the refrigerant; φ 1 is the fugacity coefficient of the refrigerant; γ 1 * is the asymmetric activity coefficient of the refrigerant, which is equal to 1 for dilute solutions. 32 Owing to the extremely low vapor pressure of lubricants, the vapor mole fraction of R32 (y 1 ) is equal to 1. Therefore, when the liquid phase mole fraction of refrigerant (x 1 ) approaches to 0, Henry's constant is calculated as…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…14 where f 1 is the fugacity of the refrigerant; φ 1 is the fugacity coefficient of the refrigerant; γ 1 * is the asymmetric activity coefficient of the refrigerant, which is equal to 1 for dilute solutions. 32 Owing to the extremely low vapor pressure of lubricants, the vapor mole fraction of R32 (y 1 ) is equal to 1. Therefore, when the liquid phase mole fraction of refrigerant (x 1 ) approaches to 0, Henry's constant is calculated as…”
Section: Resultsmentioning
confidence: 99%
“…To further evaluate the solubility behavior, we calculated the Henry’s constants of R32 in both lubricants at different temperatures. For the refrigerant/lubricant mixture, at a given temperature T and pressure p , the Henry’s constant (He 1 ) for refrigerant is expressed as where f 1 is the fugacity of the refrigerant; φ 1 is the fugacity coefficient of the refrigerant; γ 1 * is the asymmetric activity coefficient of the refrigerant, which is equal to 1 for dilute solutions . Owing to the extremely low vapor pressure of lubricants, the vapor mole fraction of R32 ( y 1 ) is equal to 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of solving simultaneous first-order ordinary equations [ 10 ], algebraic equations explicitly gain deep insight into mechanisms of length and maximum radius of lotus-type or single pores. Henry's law constants are allowed to be different at the bubble cap and top free surface, since the latter is higher than the former due to a decrease in surface curvature [ 23 ]. Solidification rates, mass transfer coefficients and partition coefficients can be varied during solidification.…”
Section: Resultsmentioning
confidence: 99%
“…Controlling fabrication of lotus-type porous materials involves adjusting parameters such as the imposed pressures of solute gases and the ambient [8,11]. As a consequence, analysis of lotus-type pores thus requires consideration of physico-chemical interfacial equilibrium constants, including Henry's and Sieverts' laws constants at liquid-gas interfaces, which are influenced by temperature, pressure, solute and solvent types, chemical reactions [14], and the curvature of the liquid-gas interface [15]. Hsiao et al [16] showed that an increase in the Henry's law constant at the cap decreases concentration at the cap.…”
Section: Introductionmentioning
confidence: 99%